Dictionary Tradition vs. Pictorial Corpora: Which Vocabulary Thematic Fields Should Be Illustrated? - Biesaga, Monika (Lexikos, 2017)
The latest research conducted by De Jong (2014) indicated that only a few European academic dictionaries, among over one hundred and fifty, use pictorial illustrations. On the other hand, it has been mentioned several times in the literature (related to both printed and electronic reference works) that visual content makes a general dictionary more attractive for the user. Therefore a new methodology, enhancing graphical strategy in lexicography, would be proposed. Firstly, a thematic division of meanings will be applied to the authentic multimodal explanations taken from two general dictionaries (verbal definition and graphical facility). As a result, commonly illustrated thematic fields will be shown along with the ones used by lexicographers in a restrained way, as well as the fields left without illustrations for some reasons. The exemplary meanings from these latest, "orphan" groups will be confronted with the query results from the authentic multimodal corpora. Such a procedure will give us some more detailed information about the obstacles connected with illustrating this particular set of senses (for example multimodal denotation and connotation problems).